The Role of Sediment Accretion and Buoyancy on Subduction Dynamics and Geometry - S. Brizzi; T. W. Becker; C. Faccenna; W. Behr; I. vanZelst; L. Dal Zilio; Y. vanDinther (Geophysical Research Letters)
Abstract Subducted sediments are thought to lubricate the subduction interface and promote faster plate speeds. However, global observations are not clear‐cut on the relationship between the amount of sediments and plate motion. Sediments are also thought to influence slab dip, but variations in subduction geometry depend on multiple factors. Here we use 2D thermomechanical models to explore how sediments can influence subduction dynamics and geometry. We find that thick sediments can lead to slower subduction due to an increase of the megathrust shear stress as the accretionary wedge gets wider, and a decrease in slab pull as buoyant sediments are subducted. Our results also show that larger slab buoyancy and megathrust stress due to thick sediments increase the slab bending radius. This offers a new perspective on the role of sediments, suggesting that sediment buoyancy and wedge geometry also play an important role on large‐scale subduction dynamics.